Polymerized human cord hemoglobin assisted with ascorbic acid as a red blood cell substitute alleviating oxidative stress for blood transfusion - Kong, Weichen; Zhou, Wentao; He, Zeng; Zhang, Xuejun; Li, Shen; Zhong, Rui; Liu, Jiaxin (Frontiers in Bioengineering and Biotechnology, 2023)
Blood transfusion is widely used in clinical settings, where considerable efforts have been devoted to develop red blood cell substitutes to overcome blood shortage and safety concerns. Among the several kinds of artificial oxygen carriers, hemoglobin-based oxygen carriers are promising due to their inherent good oxygen-binding and -loading properties. However, difficulties in prone to oxidation, production of oxidative stress, and injury in organs limited their clinical utility. In this work, we report a red blood cell substitute composed of polymerized human cord hemoglobin (PolyCHb) assisted with ascorbic acid (AA) that alleviates oxidative stress for blood transfusion. PolyCHb was first prepared from hemoglobin fetus (HbF) by chemical crosslinking. After treating with AA, there was no effect on the secondary structure and oxygen binding affinity of the PolyCHb, while the methemoglobin (MetHb) content was kept at 55%, which was much lower than that without AA treating. Moreover, the reduction of PolyCHbFe3+ was significantly promoted, and the content of MetHb could be reduced from 100% to 51% within 3 hours. In vivo study was carried out using guinea pigs that were subjected to a 50% exchange transfusion with PolyCHb(ET group) and PolyCHb assisted with AA(ET+AA group) respectively, and the results showed that PolyCHb assisted with AA inhibited the formation of hemoglobinuria, upgraded the total antioxidant capacity and downgraded the superoxide dismutase activity of kidney tissue, and lowered the expression of biomarkers for oxidative stress, e.g., malondialdehyde(ET vs ET+AA: 4.03±0.26µmol/mg vs 1.83±0.16µmol/mg), 4-hydroxy-2-nonenal(ET vs ET+AA: 0.98±0.07 vs 0.57±0.04), 8-hydroxy 2 deoxyguanosine(ET vs ET+AA: 14.81±1.58ng/ml vs 10.91±1.36ng/ml), heme oxygenase 1(ET vs ET+AA: 1.51±0.08 vs 1.18±0.05) and ferritin(ET vs ET+AA: 1.75±0.09 vs 1.32±0.04). The kidney histopathology results also demonstrated that kidney tissue damage was effectively alleviated. In conclusion, these comprehensive results suggest that PolyCHb assisted with AA has promising application for blood transfusion.